The Development of a Quadratic Functions Learning Progression and Associated Task Shells. Issue 1 (26th December 2018) - Graf, Edith Aurora; Fife, James H.; Howell, Heather; Marquez, Elizabeth
Abstract: In this report, we discuss background research on the development of student understanding of quadratic functions and present a provisional learning progression for quadratic functions and quadratic equations. We also describe task shells that are linked to the learning progression. The learning progression and task shells can be used as a starting point to develop tasks that assess student standing with respect to the theory of development. The intention is that this report should find an audience in both researchers and test developers. Abstract : Report Number: ETS RR–18‐47